THE EFFECT OF PROFITABILITY AND FINANCIAL LEVERAGE ON NET PROFIT (CASE STUDY OF BASIC INDUSTRY AND CHEMICAL SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE 2015-2017) - Riansyah, Reza Juang; Agutiyana, Sulis (Penerbit Atma Jaya Catholic University of Indonesia, 2020)
Net earning changeare movements in corporate profits calculated by subtracting current period profits from previous period profits divided by profits in the previous period. Financial ratios function to find out whether the company is healthy or not in company performance, especially financial performance as a consideration for investors to invest, which of course will have an impact on changes in company profits. This study aims to investigate the effect of profitability as proxied by Return on Assets (ROA) and financial leverage which is proxied by the Debt to Equity Ratio (DER) to changes in earnings. The object of this research is the Basic and Chemical Industry Sector listed on the Indonesia Stock Exchange in the period 2015-2017. The steps used to take samples based on predetermined criteria are called purposive sampling so there are a sample of 51 companies. This observation uses multiple linear regression analysis. This study shows that both simultaneously and partially ROA and DER affect earnings changes.